Complex Interplay between FleQ, Cyclic Diguanylate and Multiple σ Factors Coordinately Regulates Flagellar Motility and Biofilm Development in Pseudomonas putida - Jiménez-Fernández, Alicia (PLoS One, 2016)
Most bacteria alternate between a free living planktonic lifestyle and the formation of structured surface-associated communities named biofilms. The transition between these two lifestyles requires a precise and timely regulation of the factors involved in each of the stages that has been likened to a developmental process. Here we characterize the involvement of the transcriptional regulator FleQ and the second messenger cyclic diguanylate in the coordinate regulation of multiple functions related to motility and surface colonization in Pseudomonas putida. Disruption of fleQ caused strong defects in flagellar motility, biofilm formation and surface attachment, and the ability of this mutation to suppress multiple biofilm-related phenotypes associated to cyclic diguanylate overproduction suggests that FleQ mediates cyclic diguanylate signaling critical to biofilm growth. We have constructed a library containing 94 promoters potentially involved in motility and biofilm development fused to gfp and lacZ, screened this library for FleQ and cyclic diguanylate regulation, and assessed the involvement of alternative σ factors σ(N) and FliA in the transcription of FleQ-regulated promoters. Our results suggest a dual mode of action for FleQ. Low cyclic diguanylate levels favor FleQ interaction with σ(N)-dependent promoters to activate the flagellar cascade, encompassing the flagellar cluster and additional genes involved in cyclic diguanylate metabolism, signal transduction and gene regulation. On the other hand, characterization of the FleQ-regulated σ(N)- and FliA-independent PlapA and PbcsD promoters revealed two disparate regulatory mechanisms leading to a similar outcome: the synthesis of biofilm matrix components in response to increased cyclic diguanylate levels.